The analysis of the Turkish political system with respect to progress reports of the EU - Erdal, Jülide (My University, 2003)
Bu çalışmanın amacı, Avrupa Komisyonu tarafından her yıl aday ülkeler için hazırlanan ilerleme raporları doğrultusunda, Türkiye'nin politik sisteminin değerlendirilmesidir. Türkiye'nin bu yolda ne kadar gelişme gösterdiğinin anlaşılmasına da yardımcı olacaktır. Türkiye-AB ilişkilerine genel olarak bakıldığında, Avrupa standartları olan Kopenhag kriterlerine uyulmasını gerektiren AB üyeliğinin, Türkiye'nin uzun vadeli hedefi olduğu kolaylıkla anlaşılabilir. Kopenhag politik kriterleri ışığında incelendiğinde, Türk Politik Sisteminin temel organları demokratik özellikleri taşımasına rağmen, yasama, yürütme ve yargı sistemlerinin işleyişi ile ilgili bazı problemli konular mevcuttur. Bu konular, ilerleme raporlarına göre karşılaştırmalı olarak detaylı şekilde incelenmiştir. İktidara gelen hükümetlerin yapmış oldukları anayasal düzenlemeler ve uyum paketleri aracılığıyla yapılan reformlar ile Ulusal Programla ilgili olarak yapılan düzenlemeler, Türkiye'nin tam üyeliği yolunda kaydedilen önemli gelişmelerdir. Reformların ve üyelik doğrultusunda gösterilen kararlılığın devam etmesi gerekir.

ABSTRAKT The aim of this work is to evaluate the Turkish Political System with respect to the progress reports which are prepared for the candidate countries each year by the European Commission. This evaluation will also help to understand how much Turkey progress in this respect. From the general outlook of the Turkey-EU relations, it can easily be understood that being an EU member is a long-lasting goal that requires to fulfil some EU standards that are also known as Copenhagen criteria. In the light of the Copenhagen political criteria, although the fundamental organs of the Turkish Political System reflect the democratic features, some problematic issues still exist in the functioning of the legislative, the executive and the judiciary systems. These issues were all analyzed in great detail according to the progress reports through a comparative approach. The constitutional amendments made by each Turkish Government and the reforms known as harmonisation packages and Turkey's reactions with its National Program are important developments from Turkey's side on the way of the EU membership. The reforms and the determination in the direction of the membership must be continued.
Keywords: Avrupa Birliği_Türkiye